No reservations [videorecording (DVD)] - Hicks, Scott; Zeta-Jones, Catherine, 1969-; Eckhart, Aaron; Breslin, Abigail, 1996-; Nettelbeck, Sandra (Warner Home Video, 2008)
Master chef Kate Armstrong is a perfectionist who leads a regimented life, while running the kitchen of an exclusive restaurant. She revels in the sense of power and control her career affords. When Kate's sister is killed in an automobile accident, her 9-year old niece Zoe comes to live with Kate. Kate's life is turned completely upside down and she is suddenly forced to split her focus between work and family. Nick Palmer is the newly hired, fun-loving, opera-singing sous chef, whom Kate perceives as a serious rival. She then begins an impassioned struggle to rein in Nick's exuberance and maintain control over her kitchen staff. Even as they clash, Kate is drawn toward Nick, eventually coming to the realization that Nick offers something that she needs both in her restaurant kitchen and her new life with Zoe.